The SOSIAL STUDIES STUDENTS’ PERSPECTIVES ON THE USE OF GOOGLE BOOK DIGITAL LEARNING RESOURCES TO IMPROVE STUDENTS’ ACADEMIC UNDERSTANDING - Maula, Nabila Kamilatul; Safinah Nur Aini; Wahyunengsih (Institut Agama Islam Negeri Ponorogo, 2025)
As is known, digital technology has now penetrated all sectors of life. In the world of education, students must be more independent in accessing learning resources. This study aims to identify the perspectives of social studies students regarding digital learning resources such as Google Books in improving academic understanding. This study uses a quantitative method based on the results of a questionnaire to social studies students to measure students' perspectives on academic understanding, access and availability of information, motivation in learning, strategies for using Google Books, efficiency and flexibility of using Google Books, and analysis of relevant documents. The results of the study indicate that most social studies students view Google Books as a practical and applicable learning tool but have several obstacles, such as limited access to some books and the need for digital learning management strategies, and are not yet optimal in developing critical thinking skills. Google Books can broaden horizons and improve academic understanding among social studies students.